From Despair to Hope: Hope VI and the New Promise of Public Housing in America's Cities - Cisneros, Henry G; Lora Engdahl, eds; Kurt L. Schmoke (Brookings Institution Press, 2009)
Documents the evolution of HOPE VI, exploring what it accomplished replacing severely distressed public housing with mixed-income communities and where it fell short. Reveals how a program conceived to address a specific problem triggered a revolution in public housing and solidified principles that still guide urban policy today.